Calculations of dose point kernels of 64Cu in different media with PENELOPE Monte Carlo code. Issue 5 (23rd March 2019) - Tse, Jason; Geoghegan, Sean
Abstract : Purpose: The unique decay properties of copper‐64 ( 64 Cu) has made it a radionuclide of interest in theragnostic applications of nuclear medicine. This study aims to calculate the dose point kernels (DPKs) of 64 Cu in various media with PENELOPE Monte Carlo code. Methods: Monte Carlo simulations were performed using PENELOPE code (version 2014). To calculate DPKs, the simulation comprised an isotropic point radiation source positioned at the origin of a spherical object of radius 50 cm. The absorbed dose along the radial direction outwards from the point source were scored with a resolution of 20 μm. Validations were firstly performed by calculating the DPKs of monoenergetic electrons and photons in water and the results were compared against the literature values. The continuous energy spectra of the beta minus and positron emissions from 64 Cu were numerically modeled and used as inputs to the simulation. DPKs of 64 Cu were calculated in water, soft tissue, lung tissue, and cortical bone, including all emissions types. Results: The simulations have been successfully validated against literature values. The largest deviations have been observed with 10 keV monoenergetic electrons with the average and maximum dose difference of −1.01% and −10.56%. The modeled energy spectra closely compared with the average energies from Brookhaven Laboratory National Nuclear Data Centre and the combined spectral shapes from the RAdiation Dose Assessment Resource (RADAR). The DPKs of 64 Cu demonstrated different radial dose deposition in different media owing to the different physical density and effective atomic number. Conclusions: The DPKs of 64 Cu have been calculated with Monte Carlo simulations in four different media. They will be useful to study the dosimetric properties of 64 Cu‐labeled radiopharmaceuticals and perform therapeutic dose planning.